“Ono rego ono rupo”: Empirical Investigation of Intention to Purchase in Javanese Philosophy - Mariana F, R. Adjeng; Johan, Ahmad; Oktavian, Rizky Ferari; Krishti, Aghnia (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objectives: The development of technology and information is increasing, as evidenced by the substantial sales of smartphones with various designs and features. Consumers perceive that upon the launch of a new smartphone, the older model becomes obsolete, leading to high levels of electronic waste. This study aims to explore the role of environmental awareness, eco-friendly products, green trust, and consumer attitudes in environmentally friendly smartphone purchases and examines how consumer attitudes mediate these relationships.Methodology: The research adopts the theory of planned behavior and integrates it with the Javanese philosophy of ono rego ono rupo. Questionnaires were distributed to 250 respondents in several cities in Indonesia through an online platform. Structural equation modeling, using Smart-PLS software, was then employed to analyze the data. The study reveals that consumers with high environmental awareness believe that purchasing environmentally friendly smartphones can mitigate various negative aspectsFinding: The study also uncovers a positive relationship between green products, green trust, and green purchase intention, as consumers associate them with good quality, convenience, and features. Practical insights and marketing theories for smartphones are provided based on these findings.